Serum profiles of M30, M65 and interleukin‐17 compared with C‐reactive protein in patients with mild and severe acute pancreatitis. (11th September 2014) - Vlachos, Sotirios; Tsaroucha, Alexandra K.; Konstantoudakis, Georgios; Papachristou, Fotini; Trypsianis, Gregory; Schizas, Dimitrios; Vaos, Georgios; Simopoulos, Constantinos
Abstract Background Several studies state that a test of severity early in the course of acute pancreatitis is still needed. In this prospective study, an assay of the biomarkers M30 and M65 as well as of interleukin 17 (IL‐17) is investigated. Methods One hundred and fifty patients and 70 controls were evaluated. The prognostic value of M30, M65 and their ratio M30/M65 is assessed by ELISA. The same method is used for the study of IL‐17. Results At 24 h after symptom onset, the concentrations of M30 and M65 as well as their ratio, differed significantly in severe compared to mild disease (P = 0.016). C‐reactive protein (CRP) was significantly higher (P < 0.001) in severe pancreatitis on the same day. The sensitivity of M65 to show severe acute pancreatitis at 24 h was 100% for values above the cut‐off point of 428.15 U/l. The sensitivity of CRP was 100% as well. Concerning IL‐17, its concentrations were higher in patients than in the control group (P < 0.001) in the first 24 h. Conclusions Plasma concentrations of M65 and the M30/M65 ratio can be useful in predicting the severity of acute pancreatitis as early as 24 h after the onset of symptoms. The rates of IL‐17 early in the course of acute pancreatitis are indicative of the disease.